Climatogenic reaction of Robinia pseudoacacia and Pinus sylvestris within Northern Steppe of Ukraine - Y. I. Gritsan; S. A. Sytnyk; V. M. Lovynska; I. I. Tkalich (Biosystems Diversity, 2019)
Climatic changes in the environment are becoming more noticeable each year. Nonetheless, trends in the reaction of radial growth of forest trees to climate change should be studied in different climatic regions due to significant local variability in climatic conditions which are specific for any particular area. We conducted a correlation analysis of the relationship between the parameters of radial increment of black locust (Robinia pseudoacacia L.) and Scots pine (Pinus sylvestris L.) and meteorological factors of the environment in forest areas located in thenorthern steppe zone of Ukraine. We performed surveys in plantations of black locust, growing in hill slope and interfluve areas and also in sandy terrace plots of Scots pine. Over the period of intense vegetatative growth, black locust requires moisture 50% higher than the norm, and Scots pine 43% higher than the norm. It was determined that maximum increment for the studied plants occurred under the influence of a combination of factors involving reduction of the air temperature by 2.6–2.7 °С below the norm for black locust and by 2.3–2.5 °С for Scots pine. During the period of lower vegetative activity, Scots pine demonstrated lower sensitivity compared to black locust. This paper provides a statistical characteristic of the radial increment of trees in the conditions of changes in meteorological factors which limit their growth. The article provides data on multiple correlation of radial increment of the tree stands in relation to growth locations; demonstrates correlation dependency of radial increment of the studied trees on the precipitation and mean monthly temperatures over different time periods and during particular months. Radial increment of Scots pine exhibited most positive correlation with the total of precipitations throughout the period. For the stands of black locust, correlation coefficients were higher and distinguished by both positive and negative values. In the current increment of this species, a negative correlation relation was observed with the total precipitation in July, August and September, and positive correlation with the remaining months of the year. By contrast, radial increment of black locust and Scots pine positively correlated with air temperature during all time periods and particular months.